COMPARISON OF THE PROFITABILITY OF TOP 1000 FIRMS IN CANADA AND USA - Shah SAUD; Waqar BADSHAH (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
This study examines large Canadian and US firms to decompose the variation of firm profitability into year, industry, year-industry and firm components. Return on Assets (ROA), Return on Equity (ROE) and Return on Sales (ROS) provide three measures of firm profitability. For all three measures and both countries, firm effects provide the biggest contribution to the variability in firm profits with year-industry effects second, year effects third, and industry effects last. These results match those of previous studies. Comparing Canadian and US firms, firm effects explain more of the variation in the profitability of Canadian firms. Finally, the combination of industry, year and firm factors explain more the overall variation in profitability of our sample of Canadian firms than our sample of US firms.